Innovation in Medicine and Healthcare 2015 - Chen, Yen-Wei; Torro, Carlos; Tanaka, Satoshi; Howlett, Robert J.; C. Jain, Lakhmi (Smart Innovation, Systems and Technologies, 2016)
Innovation in medicine and healthcare is an interdisciplinary research area, which combines the advanced technologies and problem solving skills with medical and biological science. A central theme of this proceedings is Smart Medical and Healthcare Systems (modern intelligent systems for medicine and healthcare), which can provide efficient and accurate solution to problems faced by healthcare and medical practitioners today by using advanced information communication techniques, computational intelligence, mathematics, robotics and other advanced technologies. The techniques developed in this area will have a significant effect on future medicine and healthcare.    The volume includes 53 papers, which present the recent trend and innovations in medicine and healthcare including Medical Informatics; Biomedical Engineering; Management for Healthcare; Advanced ICT for Medical and Healthcare; Simulation and Visualization/VR for Medicine; Statistical Signal Processing and Artificial Intelligence; Smart Medical and Healthcare System and Healthcare Support System.